Truth commissions and the perpetuation of the culture of impunity in Africa : a case study of Ghana and South Africa - Hansungule, Michelo (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2003.